Answer: x=-2+2 sqrt 6 divided by 5
Hoor this helps
Step-by-step explanation:
Answer:
11x^2-8x-14
Step-by-step explanation:
(2x^2- 8x– 6)+(9x^2-8) = 11x^2-8x-14
Answer:heyyy there...the answer is b that is -12x^3+12x^2-20
Step-by-step explanation:
<h3>f(x)=
-12x^3+19x^2-5</h3><h3>g(x)=
7x^2+15</h3><h3>f(x)-g(x)=(
-12x^3+19x^2-5)-( 7x^2+15)...{while opening the bracket the sign of the second polynomial changes accordingly}</h3><h3>
it becomes -12x^3+19x^2-5-7x^2-15</h3><h3>
=-12x^3+12x^2-20</h3><h3>
HOPE IT HELPED UUUU</h3>